EVALUATION AND REDESIGN USER INTERFACE METOOCEL APPLICATION USING HUMAN CENTERED DESIGN METHOD - Muhammad Shalahuddin Aldi Baihaqi; Indra Lukmana Sardi; Rosa Reska Riskiana (STKIP PGRI Tulungagung, 2022)
Metoocel application is the name of the application from a shop that sells smartphone and laptop accessories in the Surabaya area. Metoocel application was created to make it easier for users to view product catalogs and make product purchases online through the application without the need to come to the location. However, Metoocel application has never been evaluated regarding usability since the application was created. Therefore, it is necessary to evaluate to determine the usability value of the Metoocel application. Through the initial evaluation of the study using the System Usability Scale questionnaire, the Metoocel application obtained a score of 54 so that it was included in the